PENENTUAN KONDISI OPTIMUM PENGADUKAN DALAM PROSES KOAGULASI - Tantri Mayang Arum (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2004)
This research was done at turbidity level of of 160 NTU. The research was done with jar test by varying the number of blade (2, 4 and 6 blades), diameter of the padle (55%, 65% and 75% of tank diameter), rotation speed of 190 rpm, 200 rpm and 210 rpm and distance of the padle to the tank base of ½, ¾ and 1 times of paddle diameter. This research concluded that those four factors influenced mixing physical factor equal to 90%. The main factor which affected turbidity removal were the number of the blade (46,7%) followed by the diameter of the padle (26,1%), the speed of mixing rotation (17,4%) and the distance of padle to the tank base (9,8%). Optimum condition reached by the condition of mixing using combination of 6 blades with padle’s diameter 75% to tank width, speed rotation of 210 rpm and distance of padle to tank base of ½ of the paddle diameter.